Navigating ESG Complexity through Sustainability Accounting: A Strategic Perspective for Modern Organizations - Luffi Lestari; Yusnaini Yusnaini (CV. ITTC INDONESIA, 2026)
This research is driven by the growing complexity of Environmental, Social, and Governance (ESG) in modern organizations that requires the integration of sustainability based strategies. ESG serves not only as a reporting tool but also as the foundation of organizational strategies to create sustainable value. However, its implementation still faces challenges such as the nonuniformity of indicators, differences in assessment methods, and variations in stakeholder interests. This research aims to analyze the role of sustainability accounting as a strategic approach in navigating ESG complexity. The method employed is Systematic Literature Review (SLR) using PRISMA guidelines on 60 articles from Scopus and SINTA databases, subsequently screened to 40 relevant articles. The research findings demonstrate that ESG complexity is shaped by reporting quality, interpretive differences, and inconsistent impacts on organizational performance. Sustainability accounting functions as an integrated framework that enhances transparency, information quality, and supports strategic decision making. Nonetheless, obstacles like variations in reporting standards and greenwashing risks persist. The study conclusion confirms that the integration of ESG and sustainability accounting is the key element in modern organizational strategies for achieving long term sustainability. Furthermore, these findings underscore the significance of stakeholders role in advancing transparency and reinforcing organizational legitimacy through consistent and fully integrated sustainability reporting to elevate the competitiveness of modern organizations.